THE EFFECT OF USING COMIC MEDIA TOWARDS THE DEAF CHILDREN STUDY RESULTS (Proceedings of International Conference on Special Education, 2019)
A deaf child is a child who has the disorder in the organs of hearing. The deaf children tend to be more enabling their vision (visual) to obtain the information that they need. Problems faced by deaf children are the difficulty in understanding things that are abstract and difficult to understand the verbalized things. In the curriculum of 2013, which is, the learning using a thematic approach, where in one theme consists of several subjects that are combined all at once. Viewed from the expected standard of competence, there are many demands of the abstract understanding in the curriculum, and this is one of the barriers for deaf children in achieving maximum learning results or according to the standard learning competencies. To overcome the problems faced by the deaf children, one of them is with the use of a media of learning in accordance with the progress and the problems they face, namely the comic media that is concrete visual media that are much favoured by children with entertaining nature. The use of comic media in teaching the deaf children was intended to improve the learning outcomes. The purpose of this study was to determine the learning outcomes of the deaf children at grade 1 of SLBN 2 PK PLK Cimahi Elementary School, before and after using the comic media in learning. The method used in this study is the experimental method. The study designs used are pretest and posttest one group design. Data collection techniques used is an achievement test that is the objectives test in the form of multiple-choice test with three possible answers (a, b, c). Data analysis technique used is the signed Wilcoxon rank test. The research findings indicated that the use of comic media in learning, gave the effects on learning outcomes towards the deaf children learning outcome